1996
DOI: 10.1021/ja954076k
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Size and Shape Effects in Chemical Reactions. Isotope Chemistry of the Heavy Elements

Abstract: The theory of the isotopic enrichment factor is extended to include hyperfine splitting and the nuclear field shift. It is shown that hyperfine splitting is an order of magnitude too small to explain the anomaly in the 238U/235U separation in the U(III)−U(VI) exchange reaction. The “anomalous mass effect” in this reaction and the related U(IV)−U(VI) exchange reactions are shown to be related to the nuclear field shift of the electron energy levels. Calculations of the effects of these shifts exactly reproduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
344
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(361 citation statements)
references
References 31 publications
13
344
0
4
Order By: Relevance
“…The most important driver of isotopic fractionation for the heavy element U is the nuclear volume effect, which leads to preferential enrichment of heavy U isotopes in U(IV) during U(VI) reduction (Bigeleisen 1996;Schauble, 2007;Brennecka et al, 2010;Basu, 2013;Bopp et a., 2009Bopp et a., , 2010. However, in our experiments, U is always in the (VI) oxidation state.…”
Section: U Isotope Fractionation Mechanismmentioning
confidence: 63%
“…The most important driver of isotopic fractionation for the heavy element U is the nuclear volume effect, which leads to preferential enrichment of heavy U isotopes in U(IV) during U(VI) reduction (Bigeleisen 1996;Schauble, 2007;Brennecka et al, 2010;Basu, 2013;Bopp et a., 2009Bopp et a., , 2010. However, in our experiments, U is always in the (VI) oxidation state.…”
Section: U Isotope Fractionation Mechanismmentioning
confidence: 63%
“…Nuclear field shifts have long been known in optical spectra of atoms and ions, but Bigeleisen (1) and Fujii and coworkers (8) were the first to recognize that the same phenomenon could lead to chemical fractionation of isotopes. They showed that uranium isotope separation via ion exchange columns (the Asahi process) tracked nuclear charge radii (or more specifically, the effective meansquare charge radius), rather than nuclear masses (1,8,9). Field shift effects are also expected to scale in proportion to the difference in electron densities inside the nucleus of the relevant atoms in the fractionating species (10).…”
mentioning
confidence: 99%
“…However, Fe/Ni ratios of all sample were measured, and corrected by peak strip- Thus, we feel we have extensively addressed the possibility of interferences affecting our data and 613 find no significant influence. It has been suggested (Fujii et al, 2006(Fujii et al, , 2009) that mass-independent anomalies may be the result 616 of mass-independent fractionation controlled by the nuclear field shift effect (Bigeleisen, 1996) and not As stated above, we chose iron meteorites for this study because they do not contain refractory com-627 ponents and so selective dissolution problems should be negligible. However, in general, iron meteorites 628 have longer cosmic ray exposure ages than the chondrites so we need to consider the possible perturba-629 tions due to spallation reactions.…”
mentioning
confidence: 99%